Adapting to change: an analysis of midwives' job satisfaction in the post-pandemic workplace - Mirko Prosen; Sabina Ličen (BMC Health Services Research)
Abstract Background Midwifery faces global workforce shortages exacerbated by the pandemic. Understanding job satisfaction drivers is vital for creating supportive work environments. This study explored the multifaceted nature of job satisfaction of midwives in the post-COVID era in order to understand the elements that contribute and the ones that don’t to midwives' sense of fulfilment and engagement at work. Methods Employing a quantitative descriptive methodology, a nationwide cross-sectional online survey was conducted among 169 actively practicing female midwives in Slovenia using the McCloskey-Mueller Satisfaction Scale. The survey focused on various dimensions of job satisfaction. Results Results revealed that midwives place high importance on praise/recognition, scheduling satisfaction, and work-life balance but exhibit a very weak non-significant negative relationship between job satisfaction and the importance they place on these factors. The study also identified a weak but statistically significant positive correlation between midwives' satisfaction with praise/recognition and the importance they attribute to it. Conclusions The study emphasises the need for a holistic approach in enhancing job satisfaction among midwives, fostering an environment that supports their professional development and acknowledges their contributions. It emphasizes the critical role of healthcare policymakers in developing inclusive and gender-sensitive workplace policies to improve the quality of maternal care and support the well-being and job satisfaction of midwives. Management strategies should focus on reinforcing positive work environments that facilitate professional development and work-life balance. Prioritizing these factors can improve job satisfaction, retention, and healthcare outcomes.